MODEL PENILAIAN OTENTIK DALAM PEMBELAJARAN BAHASA - Burhan Nurgiyantoro (LITERA, 2011)
This study aims to produce a validated guidebook for Authentic Assessment in Language Learning. The research activities included the guidebook development and the product was validated by three assessment experts and five teachers as stakeholders. The validation was conducted through a questionnaire and a feedbacksheet and the results were used to revise the draft to produce the final guidebook. The guidebook consists of the front page, three main chapters, references, a glossary, and an index. The results of the validation show that the guidebook is good. Conceptually it is dependable and as a guidebook it is relatively easy to use in language learning activities at school. According to the validators, it is useful to improve the language learning quality.